Methodical and hardware-software for recording and processing speech signals for diagnosis of neurological diseases - T. P. Kul; M. M. Mezhennaya; Yu. N. Rushkevich; A. N. Osipov; S. A. Likhachev; I. V. Rushkevich (Informatika)
The methodical and hardware-software on the basis of processing and analysis of speech signals for operative and objective diagnostics of neurological pathologies accompanied by speech function disorders are offered. The testing of developed methodological and software tools was carried out on the basis of the Republican Scientific and Practical Center of Neurology and Neurosurgery of the Ministry of Healthcare of Belarus and the Belarusian State University of Informatics and Radioelectronics. The results of testing revealed qualitative (based on the obtained spectrogram, kepstrogram, histogram) and quantitative (based on calculated parameters) differences between the parameters of speech signals in normal and bulbar syndrome. Preliminary results of the research confirmed the feasibility of using the methodological and hardware-software for registration and processing speech signals for diagnosis of neurological diseases.